(untitled) (Altre Modernità, 2011)
This essay will examine anthropology museums as cultural museums from the methodological approach of Cultural Studies. Within this frame, the museum acts as a mode of conservation of material culture thus revealing its immaterial consequences. In the museum, historical memories are preserved and re-enacted to articulate cultural identities in the present, to shed light on the past, and to illuminate future communal practices. After a brief survey on collections in the epoch of European geographical discoveries and on the birth of anthropology as a science in colonial times, the essay will consider the exhibition of cultural artefacts belonging to the First Nations of British Columbia in the Museum of Anthropology (MOA) in Vancouver. References to native land claims will help to understand the links between time and place, history and geography, cultural memory and land that are central to native re-constructions of identity. Through a critical reading of conventional ethnographic and anthropological criteria in museum displays, the codes of conservation and repatriation will be introduced in relation to the notion of native title and cultural property. The MOA will be used as a case in point to explore practices of negotiation with native peoples. The indigenous worldview regarding the use of objects and the performance of a living culture will be presented as opposed to the conventional aesthetic appreciation and exhibition of cultural objects. The essay will then illustrate how museums are produced and organised according to ideologically relevant standpoints in specific times and places, and how visitor-oriented practices should address a critical reading of dynamics of power and knowledge control in contemporary societies.